From the Firing at Yeonpyeong Island to a Comprehensive Solution to the Problems of Division and War in Korea - Wada Haruki (Japan Focus)
The firing by North Korea on Yeonpyeong Island dealt an unprecedented blow to the national mood. Following the June 15, 2000 declaration by Kim Dae Jung and Kim Jong Il, the feeling that no state of war existed between North and South gripped the people of South Korea. But now, islanders and military personnel died as a result of the bombardment from the North in broad daylight, and houses and facilities were destroyed. South Korean people felt shock, fear and anxiety. It’s understandable that President Lee Myung-bak, who first warned against enlarging the situation, eventually decided to take counter measures. People of South Korea have to think about how to prevent the situation from worsening, while responding to this new situation. Moreover, people throughout the region need to reflect on this situation.